Common-mode-free frequency comparison of lasers with relative frequency stability at the millihertz level - Eichenseer, M; von Zanthier, Joachim; Walther, Herbert (Optics Letters, 2005)
We report on a frequency comparison of frequency-stabilized lasers located in remote laboratories resting on different foundations. By locating the lasers in this way correlated frequency excursions of the lasers are suppressed to a high degree. The beat signal between them shows a linewidth at the hertz level for averaging times of 1 s. The optical link is established by a 100 m single-mode optical fiber where the frequency noise induced by the fiber is reduced to the level of a few tens of millihertz. One laser is stabilized onto a Fabry-Perot resonator with a long-term precision of 25 mHz (fractional frequency instability, sigma(y) = 1.2 x 10(-16)), the highest lock fidelity obtained so far to our knowledge. (c) 2005 Optical Society of America.